Adaptation of the QUANUM platform for internal audits in nuclear medicine in Brazil - Vitor Moura de Paula; Lidia Vasconcellos de Sá; Mônica Araújo Pinheiro; Gabriela I Lima; Edson Ramos de Andrade; Luis Alexandre Gonçalves Magalhães; Marcelo C Loureiro (Brazilian Journal of Radiation Sciences, 2018)
Audit is an ongoing review of all processes involving a particular service to ensure that each process is developed systematically and in accordance with specific regulations. The IAEA developed an internal audit process named QUANUM - Quality Management Audits in Nuclear Medicine being available at their website. This tool offers support to management quality audits, assisting teams in the evaluation of quality management system. QUANUM tool was developed based on the European Community guidelines and international recommendations. In order to be better applied in a country, national regulations should be followed not to generate non-conformities. Based on the current legal framework a review was performed under light of the normative items from national regulators which should be in compliance with the international recommendations. Also, national requirements not addressed by international recommendations were considered. Therefore, a single model was designed to meet both requirements, national and international standards and regulations. An Internal Audit model was elaborated which helps to quantify risk levels concerned to the process as a whole suggesting that Brazilian national regulations meet about 60 % of the international QUANUM requirements. After adaptation, a unified internal audit model was modeled where 32% are requirements from Brazilian standards, 27% from international recommendations and 41% for both Brazilian standards and international requirements. This tool systematizes and improves the quality management policy and, at last, be able to attend the Regulatory Audit, minimizing non-conformities with positive impacts on the services offered to the population.